EFFECT OF CORNUS FRUIT EXTRACTS ON OXIDATIVE STRESS IN DIABETES - A.А. Moroz; I.V. Brodyak; A.Z. Kucharska; N.O. Sybirna (Biotechnologia Acta)
The biological effects of fruits from different cultivars of the cornelian cherry under diabetes mellitus remain unclear.